Stage-specific and cell type-specific requirements of ikzf1 during haematopoietic differentiation in zebrafish - Hess, Isabell; Sagar; O'Meara, Connor; Gruen, Dominic; Schorpp, Michael; Boehm, Thomas (Scientific Reports, 2022)
The zinc finger transcription factor Ikaros1 (Ikzf1) is required for lymphoid development in mammals. Four zinc fingers constitute its DNA binding domain and two zinc fingers are present in the C-terminal protein interaction module. We describe the phenotypes of zebrafish homozygous for two distinct mutant ikzf1 alleles. The IT325 variant lacks the C-terminal two zinc fingers, whereas the fr105 variant retains only the first zinc finger of the DNA binding domain. An intact ikzf1 gene is required for larval T cell development, whereas low levels of adult lymphoid development recover in the mutants. By contrast, the mutants exhibit a signature of increased myelopoiesis at larval and adult stages. Both mutations stimulate erythroid differentiation in larvae, indicating that the C-terminal zinc fingers negatively regulate the extent of red blood cell production. An unexpected differential effect of the two mutants on adult erythropoiesis suggests a direct requirement of an intact DNA binding domain for entry of progenitors into the red blood cell lineage. Collectively, our results reinforce the biological differences between larval and adult haematopoiesis, indicate a stage-specific function of ikzf1 in regulating the hierarchical bifurcations of differentiation, and assign distinct functions to the DNA binding domain and the C-terminal zinc fingers.
CRIS-Team Scopus Importer:2023-03-23